Phthalate Exposure and Reproductive Hormone Concentrations in Pregnancy - Sathyanarayana, Sheela (2014)
BACKGROUND: Some phthalate chemicals can affect hormone physiology in utero resulting in adverse reproductive health outcomes in animal models. It is unknown whether these exposures are related to circulating maternal hormone concentrations during pregnancy. METHODS: We used multivariate linear regression to estimate associations between phthalate metabolite concentrations and concurrent serum free and total testosterone and estradiol levels in 180 pregnant women within the Study for Future Families. We also examined associations between prenatal serum hormone concentrations and anogenital outcome in infants. All analyses were adjusted for appropriate confounding variables. RESULTS: Total testosterone, free testosterone, and estradiol concentrations ranged from 8 to 406 ng/dl, 0.03 to 1.2 ng/dl, and 529 to 40600 pg/ml, respectively. We observed an inverse association between log sum di-2-ethyl hexyl phthalate (DEHP) metabolite concentrations and lower log total testosterone concentrations (−0.15, 95% CI −0.26, −0.04) and log free testosterone (−0.15, 95% CI −0.27, −0.03). This relationship persisted regardless of fetal sex. Similarly, we observed an inverse association between log mono-butyl phthalate (MBP) concentrations and log total and free testosterone concentrations in women carrying male fetuses. Mono-ethyl phthalate (MEP) concentrations were positively associated with log total and free testosterone concentrations in women carrying male fetuses (0.09, 95%CI 0.003, 0.17 and 0.10, 95% CI 0.01, 0.19 respectively). Prenatal hormone concentrations were not significantly associated with infant anogenital outcomes. CONCLUSIONS: Our preliminary data suggest that DEHP metabolite, MBP, and MEP exposures during pregnancy are associated with prenatal sex steroid hormone concentrations, but sex steroid hormone concentrations were not associated with infant reproductive outcomes.